Preparation method and application of undercut-free high-refractive-index negative OC photoresist and photocuring pattern
By using a specific high refractive index negative OC photoresist formula in the MLA structure, the undercut phenomenon and material stability problems are solved, and the photocuring pattern with high adhesion, heat resistance and light output efficiency is achieved.
Patent Information
- Application Number
- CN202411993429.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The existing MLA structure is prone to undercut in the square island pattern of high refractive index OC photoresist, which affects the process repeatability and light output efficiency. The materials of the existing solution are prone to yellowing when baked at high temperatures, release toxic gases, and lack of mechanical properties and heat resistance.
It provides a high refractive index negative OC photoresist without bottoming, and the formula includes high refractive index nanoparticles, photocurable monomers, alicyclic epoxy monomers, photoinitiators, surfactants and solvents. Through specific mass ratios and formulation design, a hydrogen bond network structure is formed to improve the adhesion and heat resistance of the film layer.
A high refractive index OC photoresist without bottoming is achieved, the adhesion and heat resistance of the photocured pattern are improved, the integrity and light output efficiency of the pattern are enhanced, and the material is stable at high temperatures, avoiding the release of toxic gases.
Smart Images

Figure CN119846903A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and relates to a preparation method and application of a high-refractive-index negative OC photoresist without undercut and a photocuring pattern. Background Art
[0002] Micro lens array (MLA) is applied to organic light emitting diode (OLED) to improve light extraction efficiency and thus screen brightness. The principle is that low refractive index OC (Over Coating) photoresist and high refractive index OC photoresist are formed into an optical structure with periodic refractive index changes through photolithography process, so that light can be converged from both sides to the center to emit light, thereby improving the forward light extraction efficiency.
[0003] The existing MLA structure mainly includes the following two structures: ① The low-refractive index photoresist is patterned, and the high-refractive index OC photoresist is coated on the entire surface of the patterned low-refractive index OC photoresist. However, due to the large internal stress of the high-refractive index OC film coated on the entire surface, it is easy to break when bent and cannot be applied to folding screens. ② The high-refractive index OC photoresist is patterned and the low-refractive index OC photoresist is coated on the entire surface, which can relieve stress and be applied to folding screens, and the light extraction efficiency is higher. However, when the high-refractive index negative OC photoresist is made into a square island pattern, undercutting (bottom peeling) usually occurs on both sides of the bottom of the pattern, forming a bevel or arc surface on the side of the bottom metal film layer. The undercut will affect the repeatability of the process, reduce the light extraction efficiency, and easily cause peeling of the subsequent Normal OC film layer, thereby affecting the product yield.
[0004] In this regard, the existing Chinese patent document (publication number: CN107446452A, publication date: December 8, 2017) discloses a composition suitable for negative development for forming an organic anti-reflective coating, which not only enhances the adhesion to the photoresist while having a high refractive index and a high etching rate, but also improves the pattern profile of undercuts, etc. However, since the composition contains an isocyanurate compound, it is easy to yellow when baked at high temperature, and it will release toxic caprolactam gas, and it is also insufficient in terms of mechanical properties and heat resistance.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The purpose of the present invention is to overcome the disadvantages of the prior art and provide a method for preparing a high-refractive-index negative OC photoresist without undercut and a photocurable pattern and application thereof.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] In the first aspect, the present invention provides a high-refractive index negative OC photoresist without undercut, which includes the following raw materials in parts by weight: 10 to 35 parts of high-refractive index nanoparticles, 1 to 10 parts of photocurable monomers, 1 to 10 parts of alicyclic epoxy monomers, 1.5 to 5 parts of photoinitiators, 0.01 to 0.5 parts of surfactants, and 25 to 75 parts of solvents.
[0009] Preferably, the high-refractive-index negative OC photoresist without undercut comprises the following raw materials by weight: 10 to 25 parts of high-refractive-index nanoparticles, 4 to 8 parts of photocurable monomers, 5 to 8 parts of alicyclic epoxy monomers, 2 to 4 parts of photoinitiators, 0.1 to 0.3 parts of surfactants, and 25 to 75 parts of solvents.
[0010] Specifically, the high refractive index nanoparticles are selected from one or two of SnO2, In2O3, TiO2, ZrO2, Al2O3, and ZnO; when any two of the high refractive index nanoparticles are mixed, the mass ratio of the two is 1: 1. Preferably, the high refractive index nanoparticles are 10 to 15 parts.
[0011] Specifically, the high refractive index nanoparticles in the present invention are modified with ligands, and acrylate ligands are connected to the surface, and are purchased from JSR, Nippon Shokubai and other companies. Further, the median particle size (D50) of the high refractive index nanoparticles is 5 to 22 nm, and the refractive index is 1.8 to 2.0. It should be noted that, on the one hand, the high refractive index nanoparticles can increase the refractive index of the photoresist, and can also affect the process and mechanism of polymerization or curing reaction, thereby indirectly regulating the internal stress. On the other hand, the high refractive index nanoparticles will produce a strong induced polarization effect on the surrounding hybrids, resulting in a significant change in dissolution behavior, thereby achieving a high sensitivity and high resolution lithography effect.
[0012] Specifically, the photocurable monomer includes a monofunctional (meth)acrylate monomer and a difunctional (meth)acrylate monomer.
[0013] Preferably, the monofunctional (meth)acrylate monomer has a viscosity of 1 to 20 cps and a glass transition temperature Tg of -60 to 110°C, and includes one or more of tetrahydrofurfuryl acrylate, cyclotrimethylolpropane formal acrylate, ethoxyethoxyethyl acrylate, 3,3,5-trimethylcyclohexyl acrylate, lauric acid acrylate, tetrahydrofurfuryl methacrylate, lauric acid methacrylate, cyclohexyl methacrylate, isobornyl acrylate, isobornyl methacrylate, isodecyl acrylate, isooctyl acrylate, isodecyl methacrylate and lauric acid methacrylate.
[0014] Preferably, the viscosity of the monofunctional (meth)acrylate monomer is 3 to 18 cps, and the glass transition temperature Tg is -60 to 15°C; more preferably, the viscosity of the monofunctional (meth)acrylate monomer is 3 to 10 cps, and the Tg is -60 to -15°C. The monofunctional (meth)acrylate monomer selected within this viscosity range and this Tg range has the characteristics of low curing shrinkage, good weather resistance, good flexibility, good water resistance, etc., and can adjust the excessive Tg of the formula caused by the addition of high refractive index nanoparticles, and can also adjust the viscosity and refractive index to improve flexibility.
[0015] Preferably, the viscosity of the bifunctional (meth)acrylate monomer at room temperature is 10 to 150 cps, and can be selected from one or more of polyethylene glycol acrylate, polyethylene glycol (200) diacrylate, polyethylene glycol (400) diacrylate, polyethylene glycol (300) diacrylate, polyethylene glycol (600) diacrylate, polyethylene glycol (200) dimethacrylate, polyethylene glycol (400) dimethacrylate, and polyethylene glycol (600) dimethacrylate.
[0016] It should be emphasized that the present invention adds monofunctional (meth)acrylate monomers and difunctional (meth)acrylate monomers in specific contents and mass ratios to the raw materials, so that the photoresist has better wettability and fluidity while maintaining cohesive strength, so that the adhesive layer is fully filled into the depressions and / or gaps on the surface of the layer (silicon nitride) to which it is adhered, thereby improving the meshing and inlaying effects, thereby increasing the contact area between the adhesive layer and the layer to which it is adhered, thereby achieving improved adhesion.
[0017] Specifically, the alicyclic epoxy monomer is an alicyclic epoxy monomer containing an unsaturated double bond and an epoxy group, wherein the unsaturated double bond specifically refers to the double bond in the acrylate functional group, and the epoxy group specifically refers to a cyclohexyl tricyclic epoxy group; the alicyclic epoxy monomer containing an unsaturated double bond and an epoxy group is specifically at least one of the structures shown in formula (1) to formula (5):
[0018]
[0019]
[0020] Among them, some functional groups (such as ether bonds and epoxy groups) in the alicyclic epoxy monomers may form hydrogen bonds with the carboxyl groups in the acrylic monomers, which can form a network structure between molecules. In addition, they can also form hydrogen bonds with the silanol groups on the surface of the substrate, thereby significantly improving the adhesion of the film layer and the heat resistance of the film layer. By increasing the adhesion, it can effectively resist the undercut caused by the internal stress of the square island pattern and improve the integrity of the pattern. In addition, the epoxy groups (-O-) on the alicyclic epoxy monomers can form a network structure between molecules. In addition, the epoxy groups (-O-) on the surface of the high-refractive nanoparticles can form a network structure between molecules ... 2-) chemical bonding reaction occurs to form a more stable connection, improve the cohesion of the film layer, and make it less likely to peel off. The oxygen atoms in the epoxy group can combine with the vacant positions on the surface of zirconium oxide to form covalent bonds or hydrogen bonds. This reaction increases the adhesion between the film layer and the substrate and reduces the desorption caused by thermal stress, mechanical stress, etc., thereby achieving physical and chemical adsorption between the two. This reaction mechanism will significantly improve the adhesion of the photocured pattern.
[0021] Furthermore, the mass ratio of the monofunctional (meth)acrylate monomer, the difunctional (meth)acrylate monomer, and the alicyclic epoxy monomer is (2-3): (3-5): (5-8). The inventors of the present application have found that under the above-mentioned specific mass ratio, not only can the volume shrinkage of the photoresist due to the decrease in the intermolecular distance during the curing process be offset, but also the dispersion of the high refractive index nanoparticles in the photoresist can be improved. Since the alicyclic epoxy resin has a tight rigid molecular structure and a large cross-linking density after curing, the film layer can have excellent tensile strength and stability; at the same time, the oxygen atoms of the alicyclic epoxy monomer may form hydrogen bonds with the hydroxyl groups on the surface of the zirconium oxide nanoparticles, which can enhance the dispersion of the nanoparticles. These non-covalent interactions can improve the adhesion between the film layer and the substrate, thereby improving the adhesion of the photocured pattern.
[0022] However, these forces are usually weaker than covalent bonds, and due to the high crosslinking density of alicyclic epoxy monomers, the cured product is easily brittle and has poor toughness. Therefore, by introducing specific low-viscosity and low-Tg monofunctional (meth)acrylates and difunctional (meth)acrylates into the photoresist formulation, the flexibility of the film layer can be improved while ensuring adhesion, the internal stress caused by curing shrinkage can be reduced, the curing rate can be increased, the ability of the photocured film to resist temperature and humidity (85°C, 85%) can be enhanced, the storage stability can be improved, and the peeling problem of the cured film can be avoided.
[0023] Specifically, the raw material of the present invention is an acrylic acid system, and no cationic photoinitiator needs to be added, and only a free radical initiator needs to be added. Therefore, the photoinitiator includes a free radical photoinitiator, such as an oxime ester photoinitiator, including 1-(4-phenylthiophenyl)-octane-1,2-dione-2-benzoic acid oxime ester (OXE-01), 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]ethanone 1-(O-acetyl oxime) (OXE-02), OXE-E12, OXPI-405, or one or more thereof.
[0024] Furthermore, in the present invention, only a free radical initiator is added without a cationic photoinitiator in order to avoid the ring-opening reaction of the alicyclic epoxy monomer for polymerization. The main polymerization reaction in the system is the photocuring reaction of the monofunctional (meth)acrylate monomer and the difunctional (meth)acrylate monomer to form a polymer. In this way, the alicyclic epoxy monomer can react more with the oxygen ions (O 2- ) undergo chemical bonding reaction to form a stable connection and increase adhesion.
[0025] Specifically, the surfactant includes: F-114, F-553, F-562 or F-570 manufactured by DIC; FC-135 or FC-170C manufactured by 3M; S-211, S-221, S-231 or S-242 manufactured by AGC; BYK-300, BYK-301, BYK-368P, BYK-302, BYK-306, BYK-310, BYK-313, BYK-320, BYK-370, BYK-377, BYK-378 or BYK-394 manufactured by BYK. The above surfactants help to reduce the surface tension and surface tension gradient of the film layer, thereby improving the wettability and adhesion of the film layer on the substrate.
[0026] Specifically, the solvent is 3-methoxy-1-butanol, diacetone alcohol, cyclohexanone, N-methyl-2-pyrrolidone, diethylene glycol ethyl methyl ether, propylene glycol methyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, triethylene glycol monomethyl ether, triethylene glycol monoethyl ether, ethyl acetate, butyl acetate, ethyl lactate, 3-methoxybutyl acetate, 3-methoxy-3-butyl acetate or propylene glycol methyl ether acetate.
[0027] In the second aspect, the present invention also provides a photocured pattern formed by the above-mentioned high-refractive-index negative OC photoresist without undercut, which can be applicable to including but not limited to microlens arrays, array flattening film patterns, protective film patterns, insulating film patterns, etc., and is particularly suitable for microlens arrays.
[0028] Specifically, the photocurable pattern is prepared by coating the photoresist material on a substrate, and then preparing the photocurable pattern by exposure and development. The specific preparation method is as follows:
[0029] Step 1, coating the above-mentioned high refractive index negative OC photoresist on a substrate; wherein the coating method adopts other coating methods such as spin coating, casting, roller coating, slit coating, etc., preferably slit coating;
[0030] Step 2: After coating, the film is heated and dried to remove volatile components to obtain a smooth film; wherein the heating temperature is 70 to 90° C.;
[0031] Step 3, irradiate the obtained adhesive film with ultraviolet light through a mask, and make the adhesive film cured by ultraviolet light contact with a developer to dissolve the unexposed area for development; after development, wash the pattern with water, blow dry with nitrogen, and then post-bake at a temperature of 70 to 100° C. for 10 to 100 minutes to obtain a photocured pattern with a thickness of 2 to 6 μm. Preferably, the thickness of the photocured pattern is 2 to 3 μm.
[0032] Finally, the present invention also provides an image display device including the above-mentioned photocurable pattern, which includes a liquid crystal display, an organic light emitting diode, a flexible display, etc., but is not limited thereto, and can also include all known image display devices that can be applied to the present technical field.
[0033] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0034] 1) The present invention adds an aliphatic epoxy monomer to the formula instead of an acrylic monomer, which can form hydrogen bonds with the photocurable monomer and the high-refractive nanoparticles to form a network structure between molecules; in addition, the aliphatic epoxy monomer can also form hydrogen bonds with the silanol group on the surface of the substrate, thereby significantly improving the adhesion of the film layer and the heat resistance of the film layer. By increasing the adhesion, the undercut caused by the internal stress of the square island pattern can be effectively resisted, thereby improving the integrity of the pattern.
[0035] 2) By regulating the weight proportions of each raw material, under a specific weight ratio, the mass ratio of monofunctional (meth)acrylate, difunctional (meth)acrylate and alicyclic epoxy monomer is controlled to be (2-3): (3-5): (5-8), which can not only offset the volume shrinkage of the photoresist due to the reduction of the intermolecular distance during the curing process, but also improve the dispersibility of high refractive index nanoparticles in the photoresist; because the alicyclic epoxy monomer has a tight rigid molecular structure, the cross-linking density is large after curing, which can make the film layer have excellent tensile strength and stability; at the same time, the oxygen atoms of the alicyclic epoxy monomer form hydrogen bonds with the hydroxyl groups on the surface of the zirconium oxide nanoparticles, which can enhance the dispersibility of the nanoparticles. These non-covalent interactions can improve the adhesion between the photoresist and the substrate, thereby improving the adhesion of the film layer. In short, the high refractive index negative OC photoresist provided by the present invention has low cost, stable performance, simple preparation method, strong operability, good repeatability, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] The accompanying drawings are incorporated in and constitute a part of this specification and, together with the description, serve to explain the principles of the present invention.
[0037] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0038] Figure 1 A flow chart of a method for preparing a photocurable pattern based on a high-refractive-index negative OC photoresist without undercut provided by the present invention;
[0039] Figure 2 The square island pattern without undercut in Examples 1 to 6 of the present invention;
[0040] Figure 3 This is the square island pattern with undercut in Comparative Examples 1 to 4 of the present invention. DETAILED DESCRIPTION
[0041] Here, exemplary embodiments will be described in detail, and the embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present invention. Instead, they are only examples consistent with some aspects of the present invention described in detail in the appended claims.
[0042] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.
[0043] Example 1
[0044] This embodiment provides a high refractive index negative OC photoresist (I) without undercut, which comprises the following raw materials in parts by weight:
[0045] 10 parts of high refractive index nanoparticles, 5 parts of photocurable monomers, 5 parts of alicyclic epoxy monomers, 2 parts of photoinitiators, 0.1 parts of surfactants, and 50 parts of solvents. Among them:
[0046] The high refractive index nanoparticles are ZrO2 with a median particle size of 5 nm and a refractive index of 1.8.
[0047] The photocurable monomers include 2 parts of tetrahydrofurfuryl acrylate and 3 parts of polyethylene glycol acrylate.
[0048] The alicyclic epoxy monomer is 3,4-epoxycyclohexylmethyl methacrylate (i.e., the structure shown in Formula 1), the photoinitiator is 1-(4-phenylthiophenyl)-octane-1,2-dione-2-benzoic acid oxime ester (OXE-01), the surfactant is BYK-313 manufactured by BYK, and the solvent is 3-methoxybutyl acetate (CAS No.: 4435-53-4).
[0049] Furthermore, the mass ratio of the monofunctional (meth)acrylate monomer, i.e., tetrahydrofurfuryl acrylate, the difunctional (meth)acrylate monomer, i.e., polyethylene glycol acrylate, and the alicyclic epoxy monomer is 2:3:5.
[0050] Example 2
[0051] This embodiment provides a high refractive index negative OC photoresist (II) without undercut, which includes the following raw materials in parts by weight:
[0052] 10 parts of high refractive index nanoparticles, 4 parts of photocurable monomers, 5 parts of alicyclic epoxy monomers, 5 parts of photoinitiators, 0.1 parts of surfactants, and 50 parts of solvents. Among them:
[0053] The high refractive index nanoparticles are a mixture of SnO2 and TiO2, with a mass ratio of 1:1, a median particle size of 15nm, and a refractive index of 2.0.
[0054] The photocurable monomers include 2 parts of ethoxyethoxyethyl acrylate and 2 parts of polyethylene glycol acrylate.
[0055] The alicyclic epoxy monomer is 3,4-epoxycyclohexylmethyl methacrylate (i.e., the structure shown in Formula 1), the photoinitiator is 1-(4-phenylthiophenyl)-octane-1,2-dione-2-benzoic acid oxime ester (OXE-01), the surfactant is BYK-313 manufactured by BYK, and the solvent is 3-methoxybutyl acetate (CAS No.: 4435-53-4).
[0056] Furthermore, the mass ratio of the monofunctional (meth)acrylate monomer, namely ethoxyethoxyethyl acrylate, the difunctional (meth)acrylate monomer, namely polyethylene glycol acrylate, and the alicyclic epoxy monomer is 2:3:5.
[0057] Example 3
[0058] This embodiment provides a high refractive index negative OC photoresist (III) without undercut, which includes the following raw materials in parts by weight:
[0059] 15 parts of high refractive index nanoparticles, 6 parts of photocurable monomers, 6 parts of alicyclic epoxy monomers, 5 parts of photoinitiators, 0.2 parts of surfactants, and 50 parts of solvents. Among them:
[0060] The high refractive index nanoparticles are SnO2 with a median particle size of 10 nm and a refractive index of 2.2.
[0061] The photocurable monomers include 2 parts of lauric acid acrylate and 4 parts of polyethylene glycol (200) diacrylate.
[0062] The alicyclic epoxy monomer has a structure shown in Formula 2, the photoinitiator is 1-(4-phenylthiophenyl)-octane-1,2-dione-2-benzoic acid oxime ester (OXE-01), the surfactant is BYK-313 manufactured by BYK, and the solvent is 3-methoxybutyl acetate (CAS No.: 4435-53-4).
[0063] Furthermore, the mass ratio of the monofunctional (meth)acrylate monomer, namely lauric acid acrylate, the difunctional (meth)acrylate monomer, namely polyethylene glycol (200) diacrylate, and the alicyclic epoxy monomer is 2:4:6.
[0064] Example 4
[0065] This embodiment provides a high refractive index negative OC photoresist (IV) without undercut, which comprises the following raw materials in parts by weight:
[0066] 15 parts of high refractive index nanoparticles, 6 parts of photocurable monomers, 6 parts of alicyclic epoxy monomers, 4 parts of photoinitiators, 0.2 parts of surfactants, and 50 parts of solvents. Among them:
[0067] The high refractive index nanoparticles are ZrO2 with a median particle size of 12 nm and a refractive index of 1.8.
[0068] The photocurable monomers include 2 parts of tetrahydrofurfuryl acrylate and 4 parts of polyethylene glycol (200) diacrylate.
[0069] The alicyclic epoxy monomer has a structure shown in Formula 2, the photoinitiator is 1-(4-phenylthiophenyl)-octane-1,2-dione-2-benzoic acid oxime ester (OXE-01), the surfactant is BYK-313 manufactured by BYK, and the solvent is 3-methoxybutyl acetate (CAS No.: 4435-53-4).
[0070] Furthermore, the mass ratio of the monofunctional (meth)acrylate monomer, i.e., tetrahydrofurfuryl acrylate, the difunctional (meth)acrylate monomer, i.e., polyethylene glycol (200) diacrylate, and the alicyclic epoxy monomer is 2:4:6.
[0071] Example 5
[0072] This embodiment provides a high refractive index negative OC photoresist (V) without undercut, which includes the following raw materials in parts by weight:
[0073] 20 parts of high refractive index nanoparticles, 8 parts of photocurable monomers, 8 parts of alicyclic epoxy monomers, 4 parts of photoinitiators, 0.2 parts of surfactants, and 50 parts of solvents. Among them:
[0074] The high refractive index nanoparticles are ZrO2 with a median particle size of 15 nm and a refractive index of 1.8.
[0075] The photocurable monomers included 3 parts of lauric acid methacrylate and 5 parts of polyethylene glycol (200) diacrylate.
[0076] The alicyclic epoxy monomer has a structure shown in Formula 4, the photoinitiator is 1-(4-phenylthiophenyl)-octane-1,2-dione-2-benzoic acid oxime ester (OXE-01), the surfactant is BYK-310 manufactured by BYK, and the solvent is diacetone alcohol (CAS No.: 123-42-2).
[0077] Furthermore, the mass ratio of the monofunctional (meth)acrylate monomer, namely lauric acid methacrylate, the difunctional (meth)acrylate monomer, namely polyethylene glycol (200) diacrylate, and the alicyclic epoxy monomer is 3:5:8.
[0078] Example 6
[0079] This embodiment provides a high refractive index negative OC photoresist (VI) without undercut, which includes the following raw materials in parts by weight:
[0080] 35 parts of high refractive index nanoparticles, 4 parts of photocurable monomers, 8 parts of alicyclic epoxy monomers, 3 parts of photoinitiators, 0.3 parts of surfactants, and 50 parts of solvents. Among them:
[0081] The high refractive index nanoparticles are ZrO2 with a median particle size of 5 nm and a refractive index of 1.8.
[0082] The photocurable monomers included 3 parts of tetrahydrofurfuryl acrylate and 5 parts of polyethylene glycol (600) diacrylate.
[0083] The alicyclic epoxy monomer has a structure shown in Formula 5, the photoinitiator is 1-(4-phenylthiophenyl)-octane-1,2-dione-2-benzoic acid oxime ester (OXE-01), the surfactant is BYK-310 manufactured by BYK, and the solvent is propylene glycol methyl ether acetate (CAS No.: 108-65-6).
[0084] Furthermore, the mass ratio of the monofunctional (meth)acrylate monomer, i.e., tetrahydrofurfuryl acrylate, the difunctional (meth)acrylate monomer, i.e., polyethylene glycol (600) diacrylate, and the alicyclic epoxy monomer is 3:5:8.
[0085] Comparative Example 1
[0086] Based on Example 1, the difference from Example 1 is that the amount of high refractive index nanoparticles used in Comparative Example 1 is 40 parts, which exceeds the aforementioned weight range of 10 to 35 parts.
[0087] Comparative Example 2
[0088] Based on Example 1, the difference from Example 1 is that the amount of high refractive index nanoparticles used in Comparative Example 2 is 5 parts, which is not within the aforementioned weight range of 10 to 35 parts.
[0089] Comparative Example 3
[0090] Based on Example 1, the difference from Example 1 is that the amount of alicyclic epoxy monomer used in Comparative Example 3 is 2 parts, that is, the mass ratio of the monofunctional (meth) acrylate monomer, namely tetrahydrofurfuryl acrylate, the difunctional (meth) acrylate monomer, namely polyethylene glycol acrylate, and the alicyclic epoxy monomer is 2:3:2.
[0091] Comparative Example 4
[0092] On the basis of Example 1, the difference from Example 1 is that the alicyclic epoxy monomer in Comparative Example 4 is 3,4-epoxycyclohexylcarboxylic acid-3',4'-epoxycyclohexylmethyl ester (CAS: 2386-87-0).
[0093] Here, the applicant needs to explain that the preparation method of the high refractive index negative OC photoresist without undercut in the present invention is: add the above raw materials into a sample bottle according to corresponding weight parts, mix and stir evenly, and filter to obtain the high refractive index negative OC photoresist.
[0094] See also Figure 1 The method for preparing a photocurable pattern based on the above-mentioned high refractive index negative OC photoresist is as follows:
[0095] Step 1, coating the above-mentioned high refractive index negative OC photoresist on a substrate; wherein the coating method adopts other coating methods such as spin coating, casting, roller coating, slit coating, etc., preferably slit coating;
[0096] Step 2: After coating, the film is heated and dried to remove volatile components to obtain a smooth film; wherein the heating temperature is 70 to 90° C.;
[0097] Step 3, irradiate the obtained adhesive film with ultraviolet light through a mask, so that the adhesive film cured by ultraviolet light is in contact with a developer to dissolve the unexposed area for development; after development, wash the pattern with water, blow dry with nitrogen, and then post-bake at a temperature of 70 to 100° C. for 10 to 100 minutes to obtain a photocured pattern with a thickness of 2 to 6 μm.
[0098] Preferably, the thickness of the photocured pattern is 2-3 μm.
[0099] Performance Testing
[0100] ① Adhesion: Use a grid cutting disc and a utility knife to cut the coating into grids; stick 3M transparent tape on the grids, and apply force to make the tape firmly stick to the coating surface and the grid area. Visually observe the peeling phenomenon and degree of the coating on the substrate to determine its ASTM grade. The ASTM grades are as follows: 5B-the cut edge is smooth, and there is no peeling on the grid edge; 4B-the peeling area in the grid area is ≤5%; 3B-the peeling area in the grid area is greater than 5% to 15%; 2B-the peeling area in the grid area is greater than 15% to 35%; 1B-the peeling area in the grid area is greater than 35% to 65%; 0B-the peeling area in the grid area is greater than 65%.
[0101] ② Undercut width: The square island patterned sample prepared by photolithography was cut into small pieces. After cutting with FIB, the undercut width l of a single side of the square island pattern with a CD (Critical Dimension) value of 15 μm was observed using SEM (in μm).
[0102] ③ Refractive index:
[0103] A 5cm×5cm×1.5μm (width×length×thickness) adhesive film is formed on the upper surface of a silicon nitride substrate. The sample is prepared according to the method for forming a solidified pattern, except that a mask is not used. The sample is tested and fitted using an ellipsometer, and the wavelength corresponding to the refractive index value is selected as 550nm.
[0104] ④Light transmittance:
[0105] The samples were prepared according to the method of forming the cured pattern except that no mask was used, and the transmittance of the cured film in the visible light range of 380 nm to 800 nm was measured by an ultraviolet-visible spectrophotometer (U-3900 Hitachi).
[0106] ⑤Curing rate:
[0107] The high refractive index negative OC photoresist without undercut was inkjet printed on a glass substrate and heated at 20 mW / cm 2 The samples were cured by UV irradiation for 5.5 s to produce a sample with a size of 3 cm × 7.5 cm × 18 μm (width × length × thickness). The ink before curing and the organic film after curing were measured by FT-IR (Nicolet iS50, Thermo-Fisher) at 1635 cm -1 (C=C) and 1720cm -1 The absorption peak area near (C=O).
[0108] Photocuring rate (%) = |1-(F / S)| × 100;
[0109] Where F is the organic film after curing at 1635cm-1 The absorption peak area near 1720cm -1 The ratio of the absorption peak areas near 1635cm -1 The absorption peak area near 1720cm -1 The ratio of the absorption peak areas nearby.
[0110] ⑥ Storage stability:
[0111] The high refractive index negative OC photoresists without undercut obtained in Examples 1 to 6 and Comparative Examples 1 to 5 were stored at -15±5°C for 120 days, then returned to room temperature, and the viscosity change was tested;
[0112] <Evaluation Criteria>
[0113] ◎Less than or equal to 0.1cps;
[0114] ○ Greater than 0.1cps and less than or equal to 0.2cps;
[0115] ×More than 0.2cps;
[0116] ⑦Dual 85 test conditions:
[0117] Temperature 85℃, relative humidity 85%, observe the film for 240 hours to see if it falls off or cracks. If no peeling occurs, it is qualified.
[0118] In order to further verify the effectiveness of the technical solution provided by the present invention, the performance of the photocurable patterns formed by the above-mentioned Examples 1 to 6 and Comparative Examples 1 to 4 was tested, and the results are shown in Table 1 below:
[0119] Table 1 Test results of photocured patterns formed in Examples 1 to 6 and Comparative Examples 1 to 4
[0120]
[0121] As shown in Table 1 above, the photocured patterns corresponding to Examples 1 to 6 have high adhesion, transmittance, refractive index and curing rate; after 240 hours of double 85 aging, there is no obvious abnormal change, which effectively reduces the deformation and cracking of the photoresist film and avoids the phenomenon of warping and deformation of the product; the storage stability is excellent, which can ensure that the photoresist pattern has high precision and integrity. At the same time, the high refractive index negative OC photoresist prepared in Examples 1 to 6 has no undercut phenomenon in the corresponding square island of the photocured pattern, such as Figure 2 shown.
[0122] However, the adhesion of Comparative Examples 1 to 4 is poor, and undercutting occurs at the bottom of the square island pattern, and the undercut width is as high as 1.53 μm. Figure 3 , the overall performance is poor. The reasons are:
[0123] The amount of high refractive index nanoparticles used in Comparative Examples 1 and 2 is not within the aforementioned required weight range of 10 to 35 parts. In Comparative Example 1, the amount of high refractive index nanoparticles used is too large, and the internal stress of the cured film layer is too large, resulting in poor adhesion, large undercut, and peeling during double 85 aging. In addition, excessive use of high refractive index nanoparticles will cause the scattering of visible light by the photocured film to become stronger, thereby resulting in lower transmittance. In Comparative Example 2, the amount of high refractive index nanoparticles used is too small, and there are too many monomers, which will cause insufficient curing, resulting in reduced adhesion of the film layer, large undercut (the bottom of the pattern is washed away by the developer due to insufficient curing), and peeling during double 85 aging.
[0124] The mass ratio (2:3:2) of the monofunctional (meth)acrylate monomer, the difunctional (meth)acrylate monomer, and the alicyclic epoxy monomer in Comparative Example 3 is not within the range of (2-3): (3-5): (5-8) required above, that is, the alicyclic epoxy monomer content is relatively low, which cannot effectively offset the internal stress generated by the photoresist curing shrinkage, resulting in reduced single film adhesion. When aged at 85°, cracking occurred at 96h, and the undercut width increased significantly. In addition, the low alicyclic epoxy monomer content is not conducive to the dispersibility of high refractive index nanoparticles in the photoresist, resulting in reduced storage stability.
[0125] In Comparative Example 4, the alicyclic epoxy monomer is 3,4-epoxycyclohexylcarboxylic acid-3',4'-epoxycyclohexyl methyl ester. Since it does not contain an acrylate functional group, it cannot participate in the main cross-linking reaction, but instead has a counter-effect. When the double 85 is aged, it falls off in 48 hours.
[0126] The above description is only a specific embodiment of the present invention, so that those skilled in the art can understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention.
[0127] It should be understood that the present invention is not limited to what has been described above and that various modifications and changes may be made without departing from its scope. The scope of the present invention is limited only by the appended claims.
Claims
1. A high refractive index negative OC photoresist without undercut, characterized in that: The raw materials are as follows, calculated by weight: 10 to 35 parts of high refractive index nanoparticles, 1 to 10 parts of photocurable monomers, 1 to 10 parts of alicyclic epoxy monomers, 1.5 to 5 parts of photoinitiators, 0.01 to 0.5 parts of surfactants, and 25 to 75 parts of solvents.
2. The high refractive index negative OC photoresist without undercut according to claim 1, characterized in that: The alicyclic epoxy monomer is an alicyclic epoxy monomer containing an unsaturated double bond and an epoxy group.
3. The high refractive index negative OC photoresist without undercut according to claim 2, characterized in that: The alicyclic epoxy monomer is at least one of the structures shown in the following formulas (1) to (5):
4. The high refractive index negative OC photoresist without undercut according to claim 1, characterized in that: The high refractive index nanoparticles are selected from one or two of SnO2, In2O3, TiO2, ZrO2, Al2O3, and ZnO.
5. The high refractive index negative OC photoresist without undercut according to claim 4, characterized in that: The median particle size of the high refractive index nanoparticles is 5 to 22 nm, and the refractive index is 1.8 to 2.
0.
6. The high refractive index negative OC photoresist without undercut according to claim 1, characterized in that: The photocurable monomers include monofunctional (meth)acrylate monomers and difunctional (meth)acrylate monomers.
7. The high refractive index negative OC photoresist without undercut according to claim 6, characterized in that: The monofunctional (meth)acrylate monomer includes one of tetrahydrofurfuryl acrylate, cyclotrimethylolpropane formal acrylate, ethoxyethoxyethyl acrylate, 3,3,5-trimethylcyclohexyl acrylate, lauric acid acrylate, tetrahydrofurfuryl methacrylate, lauric acid methacrylate, cyclohexyl methacrylate, isobornyl acrylate, isobornyl methacrylate, isodecyl acrylate, isooctyl acrylate, isodecyl methacrylate and lauric acid methacrylate.
8. The high refractive index negative OC photoresist without undercut according to claim 1, characterized in that: The photoinitiator includes an oxime ester photoinitiator, and the oxime ester photoinitiator includes any one or more of OXE-01, OXE-02, OXE-E12 or OXPI-405.
9. A method for preparing a photocurable pattern based on the high refractive index negative OC photoresist without undercut according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step 1, coating the high refractive index negative OC photoresist on a substrate; Step 2: heating and drying the film to remove volatile components to obtain a smooth film; Step 3: irradiate the obtained adhesive film with ultraviolet light through a mask, and bring the adhesive film cured by ultraviolet light into contact with a developer to dissolve the unexposed area for development, thereby completing the preparation of the desired photocured pattern.
10. An application of forming a photocurable pattern based on a high refractive index negative OC photoresist without undercut, characterized in that: The photocurable pattern is prepared by the preparation method according to claim 9 and can be applied to a microlens array, a planarization film pattern, a protection film pattern or an insulation film pattern.
Citation Information
Patent Citations
Composition for forming organic anti-reflective coating layer suitable for negative tone development
CN107446452A
Photosensitive resin composition and preparation method and application thereof
CN112859519A
Preparation method and application of flexible high-refractive-index negative OC photoresist and photocuring pattern
CN117369213A
Negative OC photoresist with low residual stress and high refractive index as well as preparation method and application of photocuring pattern
CN119126490A
Photocurable thermosetting resin composition and printed wiring board using same
KR1020080036920A